A comparative evaluation of Oratest with the microbiological method of assessing caries activity in children - Meenakshi Sundaram; Ullal Anand Nayak; Krishnakumar Ramalingam; Venugopal Reddy; Arun Prasad Rao; Mahesh Mathian (Wolters Kluwer Medknow Publications, 2013)
Aims: The aim of this study is to find out whether Oratest can be used as a diagnostic tool in assessing the caries activity by evaluating its relationship to the existing caries status and the salivary streptococcus mutans level. Materials and Methods: The study sample consists of 90 students divided into two groups. Group I (test group) and Group II (control group) consisting of 30 children for control group and 60 children for test group. The sampling of unstimulated saliva for the estimation of streptococcus mutans was done as per the method suggested by Kohler and Bratthall. The plates were then incubated. Rough surface colonies were identified as streptococcus mutans on a pre-determined area of the tip (approximately 1.5 cm 2 ) were counted for each side of spatula pressed against mitis salivarius bacitracin agar using digital colony counter. The results were expressed in colony forming units (CFU). Oratest was carried out in the same patients after the collection of salivary sample for the microbiological method to evaluate the relationship between the two tests. Statistical Analysis Used: The tests used were ANOVA, Pearson Chi-square test, Pearson's correlation analysis, Mann-Whitney U test and Student's independent t-test. Results: In the control group and test group, when the streptococcus mutans count (CFU) and Oratest time (minutes) were correlated using Pearson's correlation analysis, the streptococcus mutans counts was found to be in a statistically significant negative linear relationship with the Oratest time. When the caries status of the children, participated in the test group were correlated with mutans count (CFU) and Oratest time, caries status were found to be in a statistically significant positive linear relationship with streptococcus mutans count and in a significant negative linear relationship with Oratest time. Conclusions: The test proved to be a simple, inexpensive and rapid technique for assessing caries activity since a significant relationship exists clinically with caries status and microbiologically with the streptococcus mutans count of the individual.